Assessment of the health benefits of phytochemicals in Cynometra cauliflora based on an in silico study against Alzheimer’s disease - Jagath Illangasinghe; Heethaka. Krishantha Sameera de Zoysa; Neelamani Yapa; Thushara Chathuranga Bamunuarachchige; Viduranga Yashasvi Waisundara (Exploration of Foods and Foodomics)
Aim: Cynometra cauliflora (namnam) belongs to the family Fabaceae and is native to eastern Peninsular Malaysia. It grows well with an annual rainfall of 1,500–2,000 mm. Even though a considerable amount of research has been carried out with C. caulifora, there is a dearth of information about biomolecules that may pave the way for drug discoveries and food supplements, which is a gap addressed in this study. Methods: The study presented in this paper has identified several antimicrobial, antioxidant, and anti-inflammatory substances, and an in silico approach was used to understand the behaviors of kaempferol-3-O-rhamnoside (K-3-Rh) and β-sitosterol acetate against Alzheimer’s disease (AD). The molecular dynamics (MD) simulations were performed with the selected protein ligand complex of two natural molecules and the synthetic ligand to analyze the dynamic behaviors and binding free energy throughout the 100 ns simulation time. Further, both natural molecules that were investigated comply with Lipinski’s drug-likeness rules. Results: The docking scores of both K-3-Rh and sitosterol were found to be compatible with the synthetic AD drug molecules [donepezil analogue (H0L)] used as a reference in the study. Hence, the phytochemicals of Cynometra caulifora showed comparatively similar potency against acetylcholinesterase (AChE). Conclusions: Overall, the potential binding affinity from molecular docking and static thermodynamics features from MD simulation suggest that K-3-Rh and β-sitosterol acetate could be considered as a potential therapeutic lead to inhibit AChE leading for AD treatment.